Case report: Exploring cortico-muscular coherence during Mirror visual feedback for deafferentation pain: a proof-of-concept study - Segawa, Shiori; Osumi, Michihiro (Frontiers in Human Neuroscience, 2025)
BackgroundMirror visual feedback (MVF) has shown promise as a treatment for deafferentation pain following brachial plexus injury, yet the underlying mechanisms remain unclear. This study aimed to assess MVF’s effect on two patients with deafferentation pain by analyzing cortico-muscular coherence (CMC), a measure of functional connectivity between the brain and muscles.MethodsTwo patients with brachial plexus injuries performed wrist movements with and without a mirror, accompanied by electromyography (EMG) and electroencephalography (EEG). CMC was calculated during each condition to determine changes in the sensorimotor network.ResultsIn Patient 1, CMC increased in the beta band in the extensor carpi radialis and surrounding parietal regions during the mirror condition. In Patient 2, beta-band CMC decreased in the compensatory muscle (biceps brachii) but increased in the primary muscle (flexor carpi ulnaris) when the mirror was used. These findings suggest MVF promotes sensorimotor integration, reducing pain intensity.ConclusionMirror visual feedback (MVF) effectively enhances CMC in the contralateral sensorimotor cortex in the beta frequency band, accompanied by pain relief in the affected limb. This suggests that CMC analysis could refine deafferentation pain rehabilitation using MVF, providing a better understanding of its neural mechanisms and optimizing therapeutic outcomes. Our study underscores the potential of CMC as a valuable biomarker for monitoring and tailoring MVF interventions.